Partisipasi Mahasiswa pengapdian kepada masyarakat (KPPM) dalam kegiatan bergotong royong dilingkungan masyarakat didesa Mbinanga - Dosy Nainggolan; Frans Siregar; Sanjay Ompusunggu; Welmar Olfen Basten Barat (Abdi Jurnal Publikasi, 2023)
The community service program (PKM) is one of the activities carried out every year at HKBP Nommensen Pematangsiantar University. In this activity, students from the Faculty of Engineering and Water Resources Management had the opportunity to carry out Pkm activities which were carried out in Dairi District, Pegagan Hilir District, North Sumatra Province. Students took part in the mutual cooperation activities and observed the enthusiasm of the community in carrying out these mutual cooperation activities